Inter-Relationship Between Rheumatoid Arthritis and Periodontitis - Rajkarnikar, J; Thomas, BS; Rao, SK (Kathmandu University Medical Journal, 2014)
Background Periodontal medicine defines a rapidly emerging branch of Periodontology focusing on establishing a strong relationship between periodontal health and systemic health. It is speculated that the major common dysregulation which links Periodontitis with Rheumatoid arthritis (RA) is being played by the mediators of immune inflammatory response. Objectives To determine whether there is any relationship between periodontal disease and Rheumatoid arthritis. Methods A total of 100 patients were included for the present study which was divided into two groups: one group (cases) included 50 patients attending the Department of Orthopedics, Kasturba Medical College, Manipal who were diagnosed of Rheumatoid arthritis. Another subject population included 50 patients as controls attending the Department of Oral Medicine, Manipal College of Dental Sciences, Manipal with age and gender matched with those of rheumatoid arthritis group. Specific measures for periodontitis included plaque index, gingival index, number of missing teeth, and radiographic alveolar bone loss scores. Measures of rheumatoid arthritis included health assessment questionaires, levels of C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR). Various periodontal parameters were compared between the cases and controls. Results The average alveolar bone loss was statistically more severe in Rheumatoid arthritis (RA) group than in the controls although there were similar plaque index in both the groups. The gingival index was statistically higher in the RA group. The Erythrocyte Sedimentation Rate (ESR) and C- Reactive Protein (CRP) levels of RA patients were also significantly associated with the severity of periodontal disease. Conclusion There was a significant association between Rheumatoid arthritis and Periodontitis which may be due to a common underlying deregulation of the inflammatory response in these individuals. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11018 Kathmandu University Medical Journal Vol.11(1) 2013: 22-26